The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1590/s1516-35982001000300001
|View full text |Cite
|
Sign up to set email alerts
|

Valor nutritivo de alguns alimentos para rãs

Abstract: RESUMO -O objetivo deste trabalho foi determinar o valor nutritivo de alguns alimentos utilizados em rações de rãs, em um ensaio de digestibilidade, utilizando-se o método de alimentação forçada, com 84 rãs na fase de terminação (128,5 g ± 2 g) e 120 rãs na fase inicial (27,3 g ± 2 g), distribuídas em gaiolas de metabolismo. Quarenta rãs na fase inicial e 28 na fase de terminação permaneceram de jejum, para determinar as perdas endógenas e metabólicas. Os valores de matéria seca aparentemente metabolizável (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
0
6
2
Order By: Relevance
“…Castro et al (1998Castro et al ( , 2001 observed higher apparent metabolizable energy values of soybean meal (2,780 and 2,718 kcal/kg, respectively) for bullfrogs during the finishing phase when compared to the digestible energy (2,054.4 cal/g) obtained in the present study for the same phase of development. Probably these authors obtained different values because they used other faeces collection methods.4.3 | Apparent digestibility coefficients of crude protein (ADC CP ), gross energy (ADC GE ) and ether extract (ADC EE ) in plant energy ingredientsCorn and wheat bran exhibited low digestibility coefficients of protein and energy during the different phases of bullfrog development (Table…”
contrasting
confidence: 60%
See 4 more Smart Citations
“…Castro et al (1998Castro et al ( , 2001 observed higher apparent metabolizable energy values of soybean meal (2,780 and 2,718 kcal/kg, respectively) for bullfrogs during the finishing phase when compared to the digestible energy (2,054.4 cal/g) obtained in the present study for the same phase of development. Probably these authors obtained different values because they used other faeces collection methods.4.3 | Apparent digestibility coefficients of crude protein (ADC CP ), gross energy (ADC GE ) and ether extract (ADC EE ) in plant energy ingredientsCorn and wheat bran exhibited low digestibility coefficients of protein and energy during the different phases of bullfrog development (Table…”
contrasting
confidence: 60%
“…After the period of adaptation (one week receiving the reference diet), the animals were fasted for 48 hr to empty the digestive tube. Next, the animals were submitted to force‐feeding with 5% of the test diet in relation to their live weight (Braga et al., ; Castro et al., , ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations